Analisis Komposisi Kimia dan Evaluasi Aktivitas Antioksidan pada Ekstrak Sabut Buah Pinang (Areca catechu L.) - Wa Ode Rustiah; Andi Fatmawati; Dewi Arisanti; Alfian Alfian (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
Pinang (Areca catechu L.) is one of the plants in the Palmae family. The practice of consuming betel nut has been a long-standing tradition among some Indonesian communities. The parts of the betel nut most commonly consumed are the seeds and the young fruit husk. The husk is often mixed with betel leaf and lime, and its benefits have traditionally been used for medicinal purposes. To assess the quality and nutritional value of this food ingredient, it is necessary to conduct an analysis of macronutrient content and antioxidant potential. The use of antioxidant compounds is becoming more widespread as public understanding of their role in inhibiting degenerative diseases and premature aging grows. It is known that betel nut husk contains numerous antioxidant compounds that operate by capturing free radicals. The objective of this research is to determine the macronutrient content through proximate analysis and the antioxidant activity (IC50) of betel nut husk. Proximate analysis includes total water content (determined using thermogravimetry), total ash content (via dry ashing), total protein content (measured using the Kjeldahl method), total fat content (via Soxhlet extraction), carbohydrate content, and crude fiber content. The results obtained indicate a total water content of 9.10%, total ash content of 4.36%, total protein content of 5.92%, total fat content of 0.83%, carbohydrate content of 79.8%, and crude fiber content of 49.57%. Meanwhile, the antioxidant activity value (IC50) of the methanol fraction is 45.27 µg/mL. These test results show that the methanol extract from betel nut husk contains compounds with potential as antioxidants